Problem sceniczności w polskim przekładzie Trylogii dubrownickiej Iva Vojnovicia - Ślawska, Magdalena Ewa (Przekłady Literatur Słowiańskich, 2021)
The aim of the paper is to carry out a comparative analysis of the Polish translation of one of the most important Croatian modernist dramas A Trilogy of Dubrovnik. Ivo Vojnović’s text from 1900 was translated into Polish relatively quickly. Its first excerpts were published as early as 1904. The translation of the entire text by Helena d’Abancourt de Franqueville appeared in the periodical “Przegląd Polski” in 1906, and the book version was published in 1910. In the same year, the play was also staged in the theatre. The article focuses primarily on the problem of the performability of the translation, understood as a reflection of theatrical signs encrypted in the source text and visible in the translation, and shows what translation difficulties are associated with it.